Investment opportunities and market reaction to international joint ventures / Dina Novita Mohmad Nordin - Mohmad Nordin, Dina Novita (2007)
This study present the evidence on the role between investment opportunities and market reaction to international joint ventures focus on identification of announcements of international joint ventures between Malaysia listed firms and either foreign companies, foreign governments, or both, during the period from January 1997 to December 2007. The purpose of this study is to examine the role of investment opportunities and market reaction in explaining the effect and their impact before and after announcement international joint ventures. Secondary data being used for this study are daily stock price, and KLCI Index. This study concentrated on the 30 companies listed in Main Board of Bursa Malaysia. All the companies were selected from 1997-2007 which makes international joint ventures during the period. This study is conducted by using Microsoft excel in order to find the stock return and market return for each companies and abnormal return through Non Parametic test. Event studies measure stock price reactions to events. Price reactions are represented by abnormal returns, which are stock returns adjusted for normal daily stock price and market index movements. Researchers examine test statistics to infer whether to attribute observed abnormal returns to chance or to the event under investigation.